Li collection experiments on T-11M and T-10 in framework of Li closed loop concept - Mirnov, Sergey V.; Alekseev, Andrey G.; Belov, Alexandr M.; Djigailo, Nadejda T.; Kostina, Anastasiya N.; Lazarev, Vladimir B.; Lyublinski, Igor E.; Nesterenko, Vladislav M.; Vertkov, Aleksei V.; Vershkov, Vladimir A. (Fusion engineering and design, 2012)
► We investigated the Li collection by different type of limiters intersecting the scrape-of-layer (SOL) of T-10 and T-11M tokamaks. ► The analysis of the sample-witnesses located on Т-11М limiters showed, that 60±20% of the lithium injected during plasma operating of Т-11М had been collected by limiters. ► We believe that is the real opportunity of the tokamak plasma facing components (PFC) development on the basis of liquid lithium circulation. The concept of a steady state tokamak with plasma facing components (PFC) on the basis of liquid lithium circulation demands the decision of three tasks: lithium injection to the plasma, lithium ions collection before their deposition on the vacuum vessel and lithium returning to the injection zone. Main subject of paper is the investigations of Li collection by different types of limiters intersected the scrape-of-layer (SOL) in T-10 and T-11M tokamaks. For finding solution for this problem in T-11M and T-10, experiments have been applied with Li-, C-rail limiters and ring SS R-limiter-collector (T-11M). The efficiency of Li collection by limiters in T-11M and T-10 tokamaks was investigated by post mortem sample–witness analysis and (T-11M) by the use of the mobile graphite probe (limiter) as a recombination target in the stream of lithium ions. The characteristic depth of lithium penetration in the SOL area of T-11M is about 2cm and 4cm in SOL of T-10. The quantitative analysis of the sample–witnesses located on T-11M limiters showed that 60±20% of the lithium injected during plasma operating of T-11M had been collected by limiters. It confirms an opportunity of the lithium ions collection by limiters in tokamak SOL.